0469 The Apnea and Insomnia Research (AIR) Trial: An Interim Report. (25th May 2022) - Edinger, Jack; Manber, Rachel; Simmons, Bryan; Johnson, Rachel; Horberg, Roxane; Depew, Ann; Abraibesh, Aysha; Simpson, Norah; Eldridge-Smith, E Devon; Strand, Matthew; Espie, Colin; Kushida, Clete; et al.
Abstract: Introduction: Many sleep apnea patients suffer from comorbid insomnia disorder. Although cognitive behavioral insomnia therapy (CBTI) has proven effective for insomnia among such patients, access to trained CBTI providers remains limited. The current study is testing a digital CBTI (dCBTI) among PAP-prescribed sleep apnea patients with comorbid insomnia. Methods: Patients enrolled in this trial complete baseline measures and are randomized to dCBTI or sleep hygiene (CTRL). After 8 weeks, all patients are reassessed. Patients in the dCBTI arm who reach remission by this time point are offered no additional insomnia treatment, whereas those who do not achieve insomnia remission are randomly assigned either another 8 weeks of dCBTI or a therapist delivered CBTI (TCBTI). All groups are reassessed at the end of this second 8-week treatment phase and then again at 3- and 6-month follow-ups. This report considers changes in scores on the Insomnia Severity Index (ISI) from baseline to the end of the second 8-week treatment, as well as insomnia remission (ISI < 8) and responder rates (> 8 point decline on the ISI) of dCBTI and TCBTI relative to the CTRL. The sample for this report included the first 305 participants (mean age = 56.5±12.5 yrs.; 57.1% females). Results: Both dCBTI and TCBTI recipients showed greater (p = .0001) and comparable reductions in ISI scores from baseline to the end of the second 8-week treatment phase than did those in the CTRL group. Average ISI score improvements moved dCBTI and TCBTI recipients from moderately severe to mild insomnia symptoms. Significant group differences were noted for both the responder (X2 (2) =19.29, p < 0.0001) and remission rates (X2 (2) =13.89, p = 0.001). Responder rates for those participants switched to TCBTI (50%) were noteably higher than those continued with dCBTI (30.5%) and those in the CTRL group (19.2%); but remission rates were comparable (30.5% vs. 29.2%) and sigificantly higher than the rates shown by the CTRL group (19.2%). Conclusion: The dCBTI tested compares well with TCBTI for reducing insomnia symptoms and achieving insomnia remission in those with insomnia and sleep apnea, but insomnia responder rates may be improved by switching patients to TCBTI. Support (If Any): Funding support from the National Heart, Lung and Blood Institute, Grant # 1R01HL130559-01A1.